Case Report: The ultrasound features of acquired cystic disease-associated renal cell carcinoma: a case series - Yang, Yanrong; Chen, Hongyan; Li, Yongzhong; Zhou, Jiaojiao (Frontiers in Oncology, 2023)
Background Acquired cystic disease-associated renal cell carcinoma (ACD-RCC) is a new subtype listed by the 2016 World Health Organization (WHO) classification, which occurred in end-stage renal disease (ESRD) patients. This study will present the imaging characteristics of the four cases diagnosed with ACD-RCC. Ultrasound is expected to help detect abnormalities early in the follow-up of patients on regular dialysis, allowing patients to receive early treatment. Case presentation We searched the pathology database of our hospital for all inpatients diagnosed with ACD-RCC between January 2016 and May 2022. Pathology, ultrasound, and radiology readings are performed by experienced physicians with the title of attending physician or higher. Four cases were included in this study, all of whom were male, aged from 17 to 59. Two cases suffered from ACD-RCC in both kidneys, and kidney nephrectomies were performed. One case underwent renal transplantation, whose creatinine was back to normal, and the rest were on hemodialysis. On the pathological images, heteromorphic cells and oxalate crystals can be seen. Both ultrasound and enhanced CT showed an enhancement of the solid component of the occupancy. We followed up with outpatient and telephone visits. Conclusion In clinical work, ACD-RCC should be considered when the mass appears in the background of multiple cysts in the kidney in patients with ESRD. A timely diagnosis will help with treatment and prognosis.